Oxidation of a germanium(ii) dication to access cationic germanium(iv) fluorides. Issue 33 (6th April 2018) - Suter, Riccardo; Swidan, Ala'aeddeen; Macdonald, Charles L. B.; Burford, Neil
Abstract : Herein we describe the synthesis and characterization of the tris(1-ethyl-benzoimidazol-2-ylmethyl)amine (BIMEt3 = L) complex of Ge(ii ) 2+ and its oxidation with XeF2 to access the cationic germanium fluorides [LGeF2 ][OTf]2 and [LGeF(OTf)][OTf]2 . Abstract : The synthesis and characterization of the tris(1-ethyl-benzoimidazol-2-ylmethyl)amine (BIMEt3 = L) complex of Ge(ii ) 2+ is described. Oxidation of [LGe] 2+ with Selectfluor gives [LGeF2 ] 2+, in a process that is envisaged to involve a tricationic complex [LGeF] 3+ as an intermediate, which has been isolated by fluoride ion abstraction from [LGeF2 ] 2+ .